Identifikasi Miskonsepsi Siswa Pada Materi Reaksi Redoks Menggunakan Certainty Of Respond Indeks - Riza Raudatul Jannah; Lisa Utami (Journal of The Indonesian Society of Integrated Chemistry, 2018)
This Research aimed at identifying student misconception on Redox Reaction lesson at the tenth grade of State Vocational High School 5 Pekanbaru. It was Descriptive. Purposive sampling technique was used, and the sample were the tenth grade students of class TAV 2. Multiple choice with reasoning diagnostic test with CRI (Certainty of Response Index) column was the instrument used. Based on the research findings, it showed that there was a student misconception on Redox Reaction lesson. Sub concept was the highest misconception. The concept development of Redox Reaction lesson was 22.23%, sub concept of oxidation number was 19.05%, and sub concept of reducing and oxidation agents was 12.7%. Misconception happened because of the learning method that was teacher center, the lack of textbook reference, and the low of student learning interest. Based on the data analysis, it revealed that CRI was effective to be used to identify student misconception. Keywords: Misconception, Multiple Choice Test Reasoned Open, CRI (Certainty of Response Index), Redox Reaction Concept